Phosphate adsorption characteristics of ‘nanoclay’ separated from Indonesian volcanic tuffs - Sudadi, Untung; Imaduddin, Muhammad Anggi; Iskandar, Iskandar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
From an Indonesian volcanic tuff taken from parent material layer of an Andisols profile, it was separated ‘nanoclay’ fraction of